THE POSSIBILITIES FOR IMPROVING TEACHERS EMOTIONAL RESPONSIVENESS - Kušnere, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article “The possibilities for improving teachers' emotional responsiveness” is part of the research “Improvement of teachers' emotional responsiveness in further education”. It is devoted to a burning topic of the current times – the development of teachers' emotional responsiveness. The study is methodological in nature. The research aims to develop appropriate teaching methods and techniques, which will contribute to the development of teachers' emotional responsiveness throughout their professional education career. The purpose of the article is to describe and evaluate a set of teaching methods and techniques used in the development of teachers' emotional responsiveness. The study summarises theoretical knowledge about the role of feelings and emotions in the teaching process. It includes the author's created structured scheme of methods and techniques for the development and improvement of teachers' emotional responsiveness, which has already been successfully approved in teacher's lifelong learning. The study discusses each teaching methods' and methodological techniques' deeper meaning and effects on the development of teachers' emotional responsiveness. The author has also provided a detailed description of her methodology “What do I learn about myself?” and analyzes its influence and role in the world of educators' feelings. The results of the research are important for the requirements of the 21st century and the cultivation of healthy pedagogical thinking and habits. The results of the study show that successful continuous development of teachers' emotional responsiveness can be achieved by using such methods as “Working with symbols”, “Self-awareness” and the “Drama method”, each of which include a variety of techniques, along with the author's created ones, for example, “What do I learn about myself?”, “See! Do! Assess!” and “Practicing gratitude”.The research shows how regular work with teachers' self-study can create healthy habits, which contribute to and expand the personality growth and pedagogical thinking.